A qualitative study of how stigma influences HIV services for transgender men and women in Nigeria. (12th July 2022) - Tun, Waimar; Pulerwitz, Julie; Shoyemi, Elizabeth; Fernandez, Anita; Adeniran, Adepeju; Ejiogu, Franklin; Sangowawa, Olusegun; Granger, Krista; Dirisu, Osasuyi; Adedimeji, Adebola A.
Abstract: Introduction: Transgender men and women in Nigeria experience many barriers in accessing HIV prevention and treatment services, particularly given the environment of transphobia (including harassment, violence and discrimination) and punitive laws in the country. HIV epidemic control in Nigeria requires improving access to and quality of HIV services for key populations at high risk, including transgender men and women. We assessed how stigma influences HIV services for transgender people in Lagos, Nigeria. Methods: In‐depth interviews (IDIs) and focus group discussions were conducted with transgender men ( n = 13) and transgender women ( n = 25); IDIs were conducted with community service organization (CSO) staff ( n = 8) and healthcare providers from CSO clinics and public health facilities ( n = 10) working with the transgender population in March 2021 in Lagos. Content analysis was used to identify how stigma influences transgender people's experiences with HIV services. Results and discussion: Three main findings emerged. First, gender identity disclosure is challenging due to anticipated stigma experienced by transgender persons and fear of legal repercussions. Fear of being turned in to authorities was a major barrier to disclose to providers in facilities not affiliated with a transgender‐inclusive clinic. Providers also reported difficulty in eliciting information about the client's gender identity. Second, respondents reported lack of sensitivity among providers about gender identity and conflation of transgender men with lesbian women and transgender women with being gay or men who have sex with men, the latter being more of a common occurrence. Transgender participants also reported feeling disrespected when providers were not sensitive to their pronoun of preference. Third, HIV services that are not transgender‐inclusive and gender‐affirming can reinforce stigma. Both transgender men and women spoke about experiencing stigma and being refused HIV services, especially in mainstream public health facilities, as opposed to transgender‐inclusive CSO clinics. Conclusions: This study highlights how stigma impedes access to appropriate HIV services for transgender men and women, which can have a negative impact along the HIV care continuum. There is a need for transgender‐inclusive HIV services and competency trainings for healthcare providers so that transgender clients can receive appropriate and gender‐affirming HIV services.